Gap Analysis of Service Quality of BNI Banking Café at Manado Town Square - Stefani I. Angmalisang (Journal of International Conference Proceedings (JICP), 2019)
This study analyzes the service quality of BNI café banking at Manado Town Square. This research is using gap analysis method between consumer expectation and perception towards the service quality of BNI café banking at Manado Town Square. The café banking is the first digital banking service in Indonesia that combines the concept of banking services with café outlet. This research is a descriptive study that uses a quantitative approach. This research uses accidental sampling techniques where 100 respondents are given questionnaires. It contains 22 question items that represent five dimensions of service quality (tangible, reliable, responsiveness, assurance, and empathy). The results obtained are the score of a positive gap of 0.3 for the total of five dimensions. It means that, overall, the service quality of BNI café banking is felt by customers to exceed their expectations. Especially in the dimensions of tangible, reliable and assurance quality, these dimensions get positive gap score. The dimensions of responsiveness and empathy still do not meet the overall expectations of consumer because they get negative score. The result of this study can be an input for the management of BNI café banking at Manado Town Square, so that the quality of existing service can be improved.